Análisis de cumplimiento de las Obligaciones Tributarias de FUNCRINA durante los períodos fiscales 2015 a 2020 - Valero Ochoa, Francisco Alexis (2021)
In this case study, the fulfillment of the tax obligations of the FUNCRINA organization was analyzed, which is a non-profit institution, it was created on July 17, 1996, legally constituted with Ministerial Agreement No. 0371 before the Ministry of Justice, Human Rights and Cultos, with RUC 0992000007001, since the period 2015 and in turn it was determined the possible reasons why the organization is not complying with its duties before the tax administration that is the Internal Revenue Service. In the first place, he referred to the background of the institution in general, as well as the activity it carries out, source of its income, its obligations as a company, the date it declares, among other information; which helped to analyze the power of its tax procedures. Subsequently we find certain definitions and terms used in the study. In addition to this, we will observe the rules that control the conduct of taxpayers. We will also see a table of fines for 2021 presented by the Internal Revenue Service and the four important points that were observed in the study. According to the results obtained, a large amount of money must be paid by the Fundación Cristiana Nuevo Amanecer del Ecuador, not counting the values of these months, which are January, February and March. Because of this, FUNCRINA is recommended to: hire someone with extensive experience in accounting and tax matters; catch up on all your tax obligations and request the ease of payment.